2010
DOI: 10.1111/j.1463-1318.2009.02071.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications of transanal endoscopic microsurgery (TEMS): a prospective audit

Abstract: Transanal endoscopic microsurgery is a safe operation with a low mortality and morbidity. Pelvic sepsis is more common after excision of lesions within 2 cm of the dentate line. Ultrasonic dissection is associated with less postoperative haemorrhage than diathermy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 24 publications
2
45
1
8
Order By: Relevance
“…Our figures are found to be within the range published by other series (2% -30%) [21,[24][25][26][27][28][29], being mostly minor complications which are solved with conservative treatment. Although urinary retention is the most common complication in other studies, our main postoperative complication was bleeding, which presented in three patients, one of whom required surgical revision.…”
Section: Discussionsupporting
confidence: 77%
“…Our figures are found to be within the range published by other series (2% -30%) [21,[24][25][26][27][28][29], being mostly minor complications which are solved with conservative treatment. Although urinary retention is the most common complication in other studies, our main postoperative complication was bleeding, which presented in three patients, one of whom required surgical revision.…”
Section: Discussionsupporting
confidence: 77%
“…Postoperative complications are rare following TEM, and include postoperative bleeding (1.7-2.7%) and pelvic sepsis due to perforation (1-2.7%). The mortality associated with TEM is low (0-2%) (27). Surgical emphysema following TEM is a very rare complication (28).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, as reported in literature some authors consider the closure of the defect of the rectal wall after TEM excision as well as an essential step of the procedure, but in contrast, other authors do not consider this step mandatory in all cases. 3,10 Moreover, another important aspect, that can influence the chose to administer or not the antibiotics therapy postoperatively, could be the neoadjuvant chemo-radiotherapy (n-CRT). 3 In the Chen's et al article, patients who underwent to n-CRT are not reported, 1 even if, recently, it is possible to observe a fast increase of association of neoadjuvant therapy and transanal procedures (with TEM or other platforms).…”
Section: In Clinical Values Of Preoperative Use Of Antibiotics Inmentioning
confidence: 99%